An exploration of strategies to enhance grade 8 learners' reading comprehension skills - Matakane, Euphimia Nobuzwe (Rhodes University, Faculty of Education, Department of Education, 2013)
This thesis reports on an Action Research case study into the teaching of comprehension strategies to Grade 8 learners in a rural high school in the Eastern Cape, South Africa. The learners in this study, who were studying English as an additional language, experienced difficulties in comprehending English text. A series of six lessons were designed to teach comprehension strategies to improve the learners' performance in reading comprehension. The purpose of the intervention was to equip the learners with skills that would enable them to improve their reading comprehension and evaluate their effectiveness as readers. The intervention was also intended to assess my teaching, which was challenged by the need to deal with learners' poor levels of reading comprehension. The data was collected using the following research techniques: interviews, questionnaires, non-participant observation, learners' and researcher's journals, document analysis The data analysis revealed that a lack of resources to learn English; limited English language due to lack of exposure; and learners' lack of foundational knowledge from their primary schools were barriers to the successful teaching of comprehension strategies. Despite such barriers, however, this research provides evidence that teaching comprehension strategies can be effective if it is taught systematically, and applied continuously. Personally, I learnt that I had to modify my methods of teaching due to the response of learners to the lessons taught.
Keywords: Reading (Secondary) -- Research; Reading comprehension